The China-India dispute and the redefinition of Asian geopolitics - Ferrari Haines, Andres (2020)
The Chinese and Indian clash in June 2020 along their disputed border, despite being a long non-resolved issue, has acquired new meaning in the present global geopolitical tensions. It could erupt into a deep feud which will involve the two Asian giants in a much wider confrontation. Because their relevance in world affairs, this conflict would affect countries not only nearby, but all over the globe, amidst the substratum of the ongoing confrontation China is having with the United States. This article analyses the different aspects that are affecting this misunderstanding, linking historical concerns with recent developments. Based on the classical geopolitical analysis of the Rimland, it envisions the various constraints and impulses that will define the future of the two most populous countries of the Eurasian landmass, which are now among the largest global economies. The analysis points to the anxieties that drove China and India to the frontier clash and the mutual insecurities with regard to each other’s behavior, particularly in their relationships with third countries. In lieu of this, a solution of the dispute seems out of reach as it has become part of the present century’s geopolitical shift which is once again putting Asia in the center of the global competition.